Crystallographic Orientation Control of 1D Sb2Se3 Nanorod Arrays for Photovoltaic Application by In Situ Back‐Contact Engineering. Issue 10 (11th August 2020) - Liang, Xiaoyang; Guo, Chunsheng; Liu, Tao; Liu, Yufan; Yang, Lin; Song, Dengyuan; Shen, Kai; Schropp, Ruud. E. I.; Li, Zhiqiang; Mai, Yaohua
Abstract : Low‐dimensional (LD) crystalline inorganic semiconductors have attracted increasing interest due to their unique electrical and optical properties. The crystallographic orientation in the LD films is one of the critical parameters that determine their strong anisotropic physical properties and device performance. Antimony selenide (Sb2 Se3 ), a 1D crystalline semiconductor, is a promising absorber material for emerging photovoltaic technologies. The suitably oriented Sb2 Se3 absorbers can offer excellent carrier transport and trap‐free grain boundaries, facilitating high‐efficiency devices. The crystallographic orientation of the Sb2 Se3 light‐absorbing layer is found to be governed by the underlying layers, i.e., the back contact in substrate‐type solar cells. Herein, an in situ surface selenization treatment to the tungsten (W) back contact is applied to change the growth of Sb2 Se3 layer from a layer‐like growth mode to an island‐like growth mode. As a result, highly [hk1]‐oriented Sb2 Se3 nanorod arrays growing perpendicular to the W back‐contact surface are achieved. Moreover, the resulting tungsten selenide (WSe2 ) thin layer also acts as a hole transport layer and promotes hole extraction. Consequently, a conversion efficiency as high as 8.46% in Sb2 Se3 solar cells with substrate configuration is achieved. Abstract : Highly [hk1]‐oriented Sb2 Se3 nanorod arrays growing perpendicular to the W back‐contact surface are fabricated with in situ back‐contact engineering. A power conversion efficiency as high as 8.46% is achieved in Sb2 Se3 solar cells in substrate configuration.